Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the integral [tex]\(\int \frac{dx}{(x-1)^5}\)[/tex], we will follow a systematic approach:
1. Substitution:
We start by making a substitution to simplify the integrand. Let [tex]\( u = x - 1 \)[/tex]. Then, the differential [tex]\( du = dx \)[/tex].
The integral now becomes:
[tex]\[ \int \frac{dx}{(x-1)^5} = \int \frac{du}{u^5} \][/tex]
2. Integrate:
The above expression is a standard integral of the form [tex]\(\int u^n \, du\)[/tex], where [tex]\( n = -5 \)[/tex].
Recall the integral of [tex]\( u^n \)[/tex] is given by:
[tex]\[ \int u^n \, du = \frac{u^{n+1}}{n+1} + C \][/tex]
provided [tex]\( n \neq -1 \)[/tex].
So, for our integral:
[tex]\[ \int \frac{1}{u^5} \, du = \int u^{-5} \, du \][/tex]
Using the power rule:
[tex]\[ = \int u^{-5} \, du = \frac{u^{-5+1}}{-5+1} + C = \frac{u^{-4}}{-4} + C = -\frac{1}{4u^4} + C \][/tex]
3. Substitute back [tex]\( u = x - 1 \)[/tex]:
We now revert our substitution to express the integral in terms of [tex]\( x \)[/tex]:
[tex]\[ -\frac{1}{4u^4} + C = -\frac{1}{4(x-1)^4} + C \][/tex]
So the integral is:
[tex]\[ \int \frac{dx}{(x-1)^5} = -\frac{1}{4(x-1)^4} + C \][/tex]
When expanding this answer to make it consistent with the format of the previously determined result, our steps will result in a different form for the representation, but both results inform the solution to the integration in distinct forms.
1. Substitution:
We start by making a substitution to simplify the integrand. Let [tex]\( u = x - 1 \)[/tex]. Then, the differential [tex]\( du = dx \)[/tex].
The integral now becomes:
[tex]\[ \int \frac{dx}{(x-1)^5} = \int \frac{du}{u^5} \][/tex]
2. Integrate:
The above expression is a standard integral of the form [tex]\(\int u^n \, du\)[/tex], where [tex]\( n = -5 \)[/tex].
Recall the integral of [tex]\( u^n \)[/tex] is given by:
[tex]\[ \int u^n \, du = \frac{u^{n+1}}{n+1} + C \][/tex]
provided [tex]\( n \neq -1 \)[/tex].
So, for our integral:
[tex]\[ \int \frac{1}{u^5} \, du = \int u^{-5} \, du \][/tex]
Using the power rule:
[tex]\[ = \int u^{-5} \, du = \frac{u^{-5+1}}{-5+1} + C = \frac{u^{-4}}{-4} + C = -\frac{1}{4u^4} + C \][/tex]
3. Substitute back [tex]\( u = x - 1 \)[/tex]:
We now revert our substitution to express the integral in terms of [tex]\( x \)[/tex]:
[tex]\[ -\frac{1}{4u^4} + C = -\frac{1}{4(x-1)^4} + C \][/tex]
So the integral is:
[tex]\[ \int \frac{dx}{(x-1)^5} = -\frac{1}{4(x-1)^4} + C \][/tex]
When expanding this answer to make it consistent with the format of the previously determined result, our steps will result in a different form for the representation, but both results inform the solution to the integration in distinct forms.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.